Association of breastfeeding with mental disorders in mother and child: a systematic review and meta-analysis - Polina Bugaeva; Inna Arkusha; Rinat Bikaev; Igor Kamenskiy; Aleksandra Pokrovskaya; Yasmin El-Taravi; Valeria Caso; Alla Avedisova; Derek K. Chu; Jon Genuneit; Gabriel Torbahn; Timothy R. Nicholson; et al. (BMC Medicine, 2023)
Abstract Background Breastfeeding has long been associated with numerous benefits for both mothers and infants. While some observational studies have explored the relationship between breastfeeding and mental health outcomes in mothers and children, a systematic review of the available evidence is lacking. The purpose of this study is to systematically evaluate the association between breastfeeding and mental health disorders in mothers and children. Methods We systematically searched MEDLINE and EMBASE from inception to June 2, 2023. The inclusion criteria consisted of all studies evaluating links between breastfeeding and development of mental health disorders in children and mothers. Risk of bias was assessed using the Newcastle–Ottawa Scale (NOS) while grading of Recommendations Assessment, Development and Evaluation (GRADE) was used to assess the certainty of evidence. A random-effects meta-analysis was used if possible, to estimate the odds ratio for the association between breastfeeding and mental health outcomes. The Mantel–Haenszel method was utilised for pooling ORs across studies. Study heterogeneity was assessed using the I 2 statistic. Results Our review identified twenty-one original study. Of these, 18 focused on the association between breastfeeding and child health, assessing depressive disorders, schizophrenia, anxiety disorders, eating disorders and borderline personality disorder. Three studies evaluated the associations between breastfeeding and maternal mental health disorders. Three studies looking at outcomes in children showed no significant association between breastfeeding and occurrence of schizophrenia later in life (OR 0.98; 95% CI 0.57–1.71; I 2 = 29%). For depressive disorders (5 studies) and anxiety disorders (3 studies), we found conflicting evidence with some studies showing a small protective effect while others found no effect. The GRADE certainty for all these findings was very low due to multiple limitations. Three studies looking at association between breastfeeding and maternal mental health, were too heterogeneous to draw any firm conclusions. Conclusions We found limited evidence to support a protective association between breastfeeding and the development of mental health disorders in children later in life. The data regarding the association between breastfeeding and maternal mental health beyond the postnatal period is also limited. The methodological limitations of the published literature prevent definitive conclusions, and further research is needed to better understand the relationship between breastfeeding and mental health in mothers and children.